Calcium‐fortified foods in public health programs: considerations for implementation - Palacios, Cristina (2020)
Low calcium intake is common worldwide and can result in nutritional rickets in children and osteomalacia in adults. Calcium-fortified foods could improve calcium intake. However, there is limited calcium fortification experience, with technical and practical issues that may hamper its adoption. The objective of this landscape review is to summarize these issues to help policymakers guide the planning and design of calcium fortification as a public health strategy. One challenge is the low bioavailability of calcium salts (∼20–40%); thus, large amounts need to be added to food to have a meaningful impact. Solubility is important when fortifying liquids and acidic foods. Calcium salts could change the flavor, color, and appearance of the food and may account for 70–90% of the total fortification cost. Safety is key to avoid exceeding the recommended intake; so the amount of added calcium should be based on the target calcium intake and the gap between inadequate and adequate levels. Monitoring includes the quality of the fortified food and population calcium intake using dietary assessment methods. Calcium fortification should follow regulations, implemented in an intersectorial way, and be informed by the right to health and equity. This information may help guide and plan this public health strategy.